Phytoplankton as a Bioindicator for Evaluation of the Irrigation Water Quality near a Metal-Coating Factory - Nasihah, Mimatun; Ardyati, Ardyati; Siswanto, Dian; Retnaningdyah, Catur (Makara Journal of Science, 2024)
The irrigation water quality in Plosowahyu village, Lamongan District, Indonesia, has declined because of industrial waste disposal in irrigation canals. Specifically, waste from a metal-coating factory considerably threatens the aquatic ecosystem. To assess the impact, we evaluated water quality on the basis of phytoplankton diversity and various phys-icochemical parameters. We collected water and phytoplankton samples from four locations in Plosowahyu village: before the wastewater treatment plant (WWTP) outlet of the metal-coating factory, at this outlet, and from two sites in Wahyu River, with three repetitions at each site. The study measured several physicochemical parameters, including total dissolved solids (TDS), total suspended solids, conductivity, temperature, pH, salinity, dissolved oxygen (DO), bio-logical oxygen demand (BOD), chemical oxygen demand (COD), nitrate, orthophosphate, bicarbonate, total organic matter, sodium adsorption ratio, and lead (Pb) concentration. Phytoplankton diversity, indicated by the Shannon–Wiener index, suggested that water quality was moderately polluted at the locations before and at the WWTP outlet, lightly polluted at Wahyu River 2, and clean at Wahyu River 1. Physicochemical tests revealed that irrigation water quality parameters were below Indonesian government standards at several locations: TDS at the WWTP outlet of the metal-coating factory, DO at Wahyu River 1 and Wahyu River 2, and COD at the WWTP outlet and both Wahyu Riv-er locations. BOD, nitrate, bicarbonate, and Pb concentrations were below standards at all study sites. Principal compo-nent analysis confirmed that the metal-coating factory considerably degrades water quality. A comprehensive irriga-tion water management plan must be implemented to protect and improve irrigation water quality in Plosowahyu vil-lage.